Identifikasi Kawasan Batu Termanu sebagai Salah Satu Destinasi Wisata di Kabupaten Rote Ndao - Linda Marlince Taka; Fatrisia Yulianie (UHN IGB Sugriwa Denpasar, 2017)
Tourism activities should pay attention to several principles of management, besides the fulfillment of the tourists’ needs, the other thing to be noted is the surrounding communities without damaging the natural environment and its cultural and having a positive impact on the welfare of the local community so that it will create balance between tourism and the community. Batu Termanu regionhas tourism potential such as marine tourism, culture and history as a tourist attraction, but it has not developed properly. This study aims to determine the potential of Batu Termanu Region as a tourist destination area and to define the right strategy of tourism development here. Data analysis method used was SWOT analysis. The result of this study showed that Batu Termanu Region has the potential of natural, culture, history appeal and kinship community, but it was not fully supported yet by the facilities, infrastructure, transport and friendliness that support tourist activities. The right strategies in developing this area were to build all of the facilities and good infrastructure, promotion, making travel packages, to involve the community in the development process.